Study of the Impact of Marriage at a Young Age on Reproductive Health: A Qualitative Study in Purwakarta Regency, Indonesia - Suciati, Tia (Archives of The Medicine and Case Reports, 2024)
Marriage at a young age is one of the reproductive health problems that needs attention. This research aims to examine the impact of marriage at a young age on reproductive health in Purwakarta Regency, Indonesia. This research used a cross-sectional survey method with a sample of 200 married couples who married at a young age. Data was collected through questionnaires and interviews. The research results show that married couples who marry at a young age have a higher risk of experiencing unwanted pregnancies, pregnancy and childbirth complications, and sexually transmitted infections. Apart from that, married couples who marry at a young age also have a higher risk of experiencing domestic violence. Based on the results of this research, it can be concluded that marriage at a young age has a negative impact on reproductive health. Therefore, efforts need to be made to prevent marriage at a young age.